SOCIO-PSYCHOLOGICAL CHARACTERISTICSOF LVIV UNIVERSITY OF THE THIRD AGE LISTENERS ADAPTABILITY - Оstrovska Kateryna (Journal of Education Culture and Society, 2020)
The paper deals with investigations of social-psychological adaptability peculiarities of elderly people in Lviv (Ukraine). These personal performances are compared for the people who study and those who are not L’viv University of Third Age (LUTA) listeners. The results of investigation have shown that participation of elderly people in LUTA allows them to decrease the solitude feeling and to increase the socio-psychological adaptability as well as the stress resistance level.